Deciphering the epidemiological dynamics: Toxoplasma gondii seroprevalence in mainland China’s food animals, 2010-2023 - Yang, Zipeng; Yuan, Hao; Nie, Linchong; Wen, Qingyuan; Li, Haoxin; Yang, Liulu; Song, Yining; Luo, Xun; Zhang, Xiu-Xiang; Yuan, Zi-Guo (Frontiers in Cellular and Infection Microbiology, 2024)
Background Toxoplasma gondii (T. gondii) is a significant protozoan pathogen among food animals. Despite the threat to public health by T. gondii infections, there’s limited understanding of its seroprevalence and trends in food animals across mainland China. This study aimed to estimate the seroprevalence of T. gondii infections among swine, sheep, goats, chickens, and cattle in mainland China from 2010 to 2023. Methods We searched cross-sectional studies published between 2010 and 2023 that reported the prevalence of T. gondii in food animals from databases including PubMed, Embase, Web of Science, China Biology Medicine Disc (CBM), China National Knowledge Infrastructure (CNKI), Wanfang data, and the China Science and Technology Journal Database (CQVIP). We performed subgroup analyses to explore the impact of different factors on the seroprevalence of T. gondii. Pooled estimates of T. gondii seroprevalence were calculated with a random-effects model. Results An analysis of 184 studies involving 211985 animals revealed a T. gondii overall seroprevalence of 15.3% (95% CI: 13.1-17.8). Although the seroprevalence of food animals across mainland China was relatively stable from 2010 to 2023, notable variations were observed across different animal types and regions (P < 0.01), along with changes in geographical distribution. Sample type, detection method, animal age, and history of abortion were identified as key risk factors for T. gondii seroprevalence. Conclusion The study conducted a meta-analysis on the seroprevalence of T. gondii in mainland China’s Food Animals from 2010 to 2023, and identified key risk factors. These findings advance our understanding of T. gondii infection dynamics, offering critical insights for developing control strategies and guiding public health policies.